2019
DOI: 10.1007/s40565-019-0541-6
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven failure diagnosis in transmission protection system with multiple events and data anomalies

Abstract: To guarantee the reliable power supply, the expected operation of all the components in the power system is critical. Distance protection system is primarily responsible of isolating the faulty section from the healthy part of the grid. Failure in protection devices can result in multiple conflicting alarms at the power grid operation center and complex events analysis to manually find the root cause of the observed system state. If not handled in time, it may lead to the propagation of the faults/failures to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Finally, a model to find the root causes of the observed events assisted by the cyber log data from the protection devices are developed. Anomaly detection in PMUs is further discussed in [ 62 ] to detect the root cause of the failure in the transmission protection system, and it is shown that ensemble models are superior to stand‐alone methods.…”
Section: Solutions For Minimising Impact Of Covid‐19mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a model to find the root causes of the observed events assisted by the cyber log data from the protection devices are developed. Anomaly detection in PMUs is further discussed in [ 62 ] to detect the root cause of the failure in the transmission protection system, and it is shown that ensemble models are superior to stand‐alone methods.…”
Section: Solutions For Minimising Impact Of Covid‐19mentioning
confidence: 99%
“…Three infected IT security engineers at a nuclear power plant were quarantined for 14 days [19], increasing the risks that threaten normal operations. State of the art technologies in AI and ML can aid in reducing humans' direct involvement with overseeing, maintaining, and failure detection [57]. Protection systems are always of the highest priority in the energy industry.…”
Section: Impact Of Covid-19 On the Power Grid Operationmentioning
confidence: 99%
“…Data pre-processing and measurement denoising is a significant step which needs to be accomplished prior to investigation of any physical or cyber-induced events throughout the system [1]. A proper BDD technique is of enormous concern in such Distribution System (DS) applications as State Estimation (SE) [2], fault classification [3], fault location identification [4], and situational awareness [5]. [6] presents a comprehensive study on different ML-based approaches for distribution level disturbance analysis with regard to efficacy examination and performance evaluation of each technique.…”
Section: B Related Workmentioning
confidence: 99%
“…In [13], when processing the training set of SVM, a clustering method is used to identify the abnormal data, and the separated abnormal data are directly removed, which may destroy the continuity and integrity of the data. Reference [14] proposes two means to address the measurement anomalies: one is flagging them and the other is replacing the anomaly with the average value of the data points lying around. In [15], the abnormal data are imputed, utilizing the artificial neural network (ANN) and autoregressive exogenous input (ARX) models.…”
Section: Introductionmentioning
confidence: 99%
“…In state-of-the-art works, the main concern for missing data recovery is accuracy [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. For realistic power grids, the number of electrical infrastructures reaches tens or hundreds of thousands, generating nearly ten or hundred million monitoring data every year.…”
Section: Introductionmentioning
confidence: 99%